2012
DOI: 10.1097/cji.0b013e318270e135
|View full text |Cite
|
Sign up to set email alerts
|

Combined TLR Stimulation With Pam3Cys and Poly I

Abstract: The cytokines granulocyte macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-4 are frequently used for generating dendritic cells (DCs) for therapeutic vaccination against cancer. These in vitro DCs share several characteristics with inflammatory monocyte-derived DCs in vivo. In contrast, culture of bone marrow cells in Flt3-ligand (Flt3L) generates a heterogeneous population of DCs, which comprise conventional DCs (cDCs) and plasmacytoid DCs similar to the steady-state populations found in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…It was also shown that combinations of TLR 2, 3 and 9 ligands could enhance DC function and the induction of T cell immunity following vaccination [50]. Finally, a DC based vaccine delivered with TLR3 and TLR 2 provided enhanced protection to mice challenged with tumor [51]. …”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that combinations of TLR 2, 3 and 9 ligands could enhance DC function and the induction of T cell immunity following vaccination [50]. Finally, a DC based vaccine delivered with TLR3 and TLR 2 provided enhanced protection to mice challenged with tumor [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Immunopotentiators optimize DC-based vaccines and enhance production of the type-1 T-cell mediator IL-12. These include toll-like receptor agonists poly I:C, LPS, Pam3Cys and R848 [136138]. The final study to be discussed in this review designed a vaccine with hyperstimulatory potential by loading DCs with a poxvector containing genes for CEA and other costimulatory molecules, including CD80.…”
Section: Directing the Immune System Against Metastatic Crcmentioning
confidence: 99%
“…(NCT01984892); (2) in melanoma patients, who receive Hiltonol™ to improve the immunogenicity of a personalized, neoantigen-targeting peptide-based vaccine (NCT01970358); (3) in individuals with glioblastoma, who are treated with Hiltonol™ as adjuvant to a multipeptide-based vaccine (IMA950) 160 given in combination with temozolomide-based radiochemotherapy 82 , 161 (NCT01920191); (4) in cutaneous T-cell lymphoma patients, receiving Hiltonol™ to boost the therapeutic potential of radiation therapy coupled to the histone deacetylase inhibitor romidepsin 162 - 165 (NCT02061449); and (5) in B-cell lymphoma patients, who are concurrently treated with recombinant human FLT3 ligand (FLT3L, also known as CDX-301) 166 - 168 i.t. plus low-dose radiation therapy in the attempt to recruit DCs to neoplastic lesions and thus promote clinically relevant anticancer immune responses (NCT01976585).…”
Section: Update On Ongoing Clinical Trialsmentioning
confidence: 99%